2014
DOI: 10.1016/j.dss.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment analysis: Bayesian Ensemble Learning

Abstract: The huge amount of textual data on the Web has grown in the last few years rapidly creating unique contents of massive dimension. In a decision making context, one of the most relevant tasks is polarity classification of a text source, which is usually performed through supervised learning methods. Most of the existing approaches select the best classification model leading to over-confident decisions that do not take into account the inherent uncertainty of the natural language. In this paper, we pursue the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(57 citation statements)
references
References 13 publications
0
51
0
6
Order By: Relevance
“…Bayes tabanlı ensemble yöntemini diğer ensemble yöntemleri ile kıyaslamak için NB, ME, DVM ve Koşullu Rasgele Alanlar sınıflama algoritmalarını kullanarak altı farklı veri seti ile analiz yapmışlardır. Bu analizin sonucunda Bayes tabanlı yöntemin başarı oranını artırdığı ve zaman kazandırdığı görülmüştür [13]. Da Silva vd.…”
Section: Gi̇ri̇ş (Introduction)unclassified
“…Bayes tabanlı ensemble yöntemini diğer ensemble yöntemleri ile kıyaslamak için NB, ME, DVM ve Koşullu Rasgele Alanlar sınıflama algoritmalarını kullanarak altı farklı veri seti ile analiz yapmışlardır. Bu analizin sonucunda Bayes tabanlı yöntemin başarı oranını artırdığı ve zaman kazandırdığı görülmüştür [13]. Da Silva vd.…”
Section: Gi̇ri̇ş (Introduction)unclassified
“…They showed that random subspace has the better comperative results. Fersini et al [20] proposed a novel ensemble method based on Bayesian Model Averaging for sentiment analysis of user reviews. They showed their model outperformed the other approaches such as bagging.…”
Section: Related Workmentioning
confidence: 99%
“…The performance of the machine learning technique depends on the effectiveness of the selected method for feature extraction. Among the most used methods are bag of words [13], TF-IDF [14], -grams (unigrams, bigrams, and trigrams) [11,15], features based on POS tagging [16], and features based on dependency rules [17].…”
Section: Related Workmentioning
confidence: 99%